1992
DOI: 10.1002/jcp.1041500207
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor and transforming growth factor‐alpha decrease gamma interferon receptors and induction of intercellular adhesion molecule (ICAM‐1) on cultured keratinocytes

Abstract: The link between the epidermal keratinocytes of the skin and the activated T lymphocytes of the immune system is mediated by a variety of cytokines, including gamma interferon (IFN-y). We studied the influence of keratinocyte mitogens such as transforming growth factor-alpha (TGF-a), epidermal growth factor (EGF), and somatomedin-C (SM-C) on the ligand binding of '2P-labelled IFN-y to cultured keratinocytes derived from normal appearing adult. human skin. Keratinocytes placed in a medium devoid of mitogens bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Since EGFR signaling might downregulate IFNγ receptor1 (IFNRI) (25), providing a mechanism for synergistic effects of EGFR blockade with IFNγ for STAT1-mediated HLA upregulation, we evaluated levels of IFNRI after cetuximab treatment. Indeed, cetuximab increased the expression of IFNRI in several HNC cell lines tested, in an EGFR-dependent fashion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since EGFR signaling might downregulate IFNγ receptor1 (IFNRI) (25), providing a mechanism for synergistic effects of EGFR blockade with IFNγ for STAT1-mediated HLA upregulation, we evaluated levels of IFNRI after cetuximab treatment. Indeed, cetuximab increased the expression of IFNRI in several HNC cell lines tested, in an EGFR-dependent fashion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These same ligands can attenuate the induction of MHCII genes by IFN-g (14). On the basis of this, we hypothesized that the transactivation of the EGFR following IFN-g exposure might establish a negative feedback loop and thereby limit MHCII molecule expression which is tightly regulated (15).…”
Section: Resultsmentioning
confidence: 99%
“…These same ligands can repress the induction of MHCII molecules by IFN-g (14). Therefore, we reasoned that inhibition of protease activity would block the release of EGFR ligands following IFN-g exposure and lead to a more robust induction of MHCII molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Prior reports have demonstrated that if keratinocytes are treated simultaneously with an EGFR ligand and IFNγ, there is an attenuation of MHCII induction. 11 Based upon this, we hypothesized that EGFRIs would have the opposite effect and would therefore augment MHCII induction by IFNγ. Because MHCII gene expression is largely regulated at the level of transcription, we focused our initial studies on a critical transcriptional regulator of MHCII molecule expression, the MHCII transactivator named CIITA.…”
Section: A Recent Study From Our Laboratory Demonstrated That Epidermmentioning
confidence: 99%